A Micromechanics Model for Bread Dough - Mohammed,MAP; Tarleton,E; Charalambides,MN; Williams,JG (American Institute of Physics, 2015)
The mechanical behaviour of dough and gluten was studied in an effort to investigate whether bread dough canbe treated as a two phase (starch and gluten) composite material. The dough and gluten show rate dependent behaviourunder tension, compression and shear tests, and non-linear unloading-reloading curves under cyclic compression tests.There is evidence from cryo-Scanning Electron Microscopy (SEM) that damage in the form of debonding between starchand gluten occurs when the sample is stretched. A composite finite element model was developed using starch as fillerand gluten as matrix. The interaction between the starch and gluten was modelled as cohesive contact. The finite elementanalysis predictions agree with trends seen in experimental test data on dough and gluten, further evidence that debondingof starch and gluten is a possible damage mechanism in dough.